2014
DOI: 10.1590/1414-431x20143713
|View full text |Cite
|
Sign up to set email alerts
|

Influence of exercise modality on agreement between gas exchange and heart rate variability thresholds

Abstract: The main purpose of this study was to investigate the level of agreement between the gas exchange threshold (GET) and heart rate variability threshold (HRVT) during maximal cardiopulmonary exercise testing (CPET) using three different exercise modalities. A further aim was to establish whether there was a 1:1 relationship between the percentage heart rate reserve (%HRR) and percentage oxygen uptake reserve (%V˙O2 R) at intensities corresponding to GET and HRVT. Sixteen apparently healthy men 17 to 28 years of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
1
6
1
Order By: Relevance
“…This confirms that Vth determine during cycling test appears before walking test. In the same vein, Cunha et al (2014) showed that maximal HR obtained during walking was higher than maximal HR during cycling and with a difference of 7 bpm (Cunha et al, 2014). This supports the idea that HR SDT6 (determined by auto-calibrated walking test) was consistent with HR Vth (determined during incremental exercise test on ergocycle) and with to a fluctuation of HR between both tests close to previous studies (Cunha et al, 2014;Mahler et al, 2011).…”
Section: Discussionsupporting
confidence: 86%
“…This confirms that Vth determine during cycling test appears before walking test. In the same vein, Cunha et al (2014) showed that maximal HR obtained during walking was higher than maximal HR during cycling and with a difference of 7 bpm (Cunha et al, 2014). This supports the idea that HR SDT6 (determined by auto-calibrated walking test) was consistent with HR Vth (determined during incremental exercise test on ergocycle) and with to a fluctuation of HR between both tests close to previous studies (Cunha et al, 2014;Mahler et al, 2011).…”
Section: Discussionsupporting
confidence: 86%
“…Recent studies have used time and frequency domains of heart rate variability (HRV) as a measure of autonomic cardiac nervous system (i. e. parasympathetic and sympathetic modulation) at rest or during exercise [2]. They have proposed that the LT and GET would correlate with a specific marker of vagal withdrawal, denominated HRV threshold (HRVT) [5,8,19]. Indeed, accumulated evidence has suggested that HRVT might be a reliable and simple tool to estimate GET [4-6, 10, 11, 19].…”
Section: Introduction ▼mentioning
confidence: 99%
“…Indeed, the findings of Gaskill et al [13] showed that the combined method not only results in fewer rejected data but also improves the accuracy of the GET determination and greatly reduced the number of large errors when compared with individual methods of ventilatory threshold determination. With the exception of 2 previous studies [8,19], most studies adopted individual methods to evaluate the ventilatory threshold [4,6,10,11,29]. Therefore it is not difficult to understand that such inherent error would have important practical consequences for the validity and reliability of HRVT method from the evaluation for determining the GET.…”
mentioning
confidence: 99%
“…The RR interval (iRR) signals obtained from the electrical cardiac activity and captured by the telemetric cardiac monitor V800 (Polar OY, Finland) were exported to Kubios software (Kuopio, Finland) to calculate the HRV indices during the GA-T. The sampling frequency was 1,000 Hz, and any iRR with a difference > 20% from the previous interval was automatically filtered out by the program (20).…”
Section: Autonomic Nervous System Activitymentioning
confidence: 99%